2008
DOI: 10.1098/rspb.2008.0199
|View full text |Cite
|
Sign up to set email alerts
|

Parent–offspring conflict and co-adaptation: behavioural ecology meets quantitative genetics

Abstract: The evolution of the complex and dynamic behavioural interactions between caring parents and their dependent offspring is a major area of research in behavioural ecology and quantitative genetics. While behavioural ecologists examine the evolution of interactions between parents and offspring in the light of parent-offspring conflict and its resolution, quantitative geneticists explore the evolution of such interactions in the light of parent-offspring co-adaptation due to combined effects of parental and offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 78 publications
(125 reference statements)
2
112
0
Order By: Relevance
“…As always, solving the conflict would require additional assumptions. A resolution model of our battleground portrayal could be conceived by incorporating signalling [3,5,17] or developmental limits imposed on the form of the demand and supply function [11,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As always, solving the conflict would require additional assumptions. A resolution model of our battleground portrayal could be conceived by incorporating signalling [3,5,17] or developmental limits imposed on the form of the demand and supply function [11,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The specific behavioural traits underlying POC are best understood as reaction norms [11]. This is why our model assumes parents to express supply function genes that regulate resource supply to offspring and that offspring express demand function genes that regulate resource demand from parents [12].…”
Section: Modelmentioning
confidence: 99%
“…Reaction norms are particularly relevant to the study of behaviours as they are often labile, and thus responses often vary greatly with environmental and social conditions (Smiseth et al 2008). Dingemanse et al (2010a,b) suggested that the general framework for describing reaction norms provided by quantitative genetics could be extended to those behaviours observed as components of behavioural syndromes.…”
Section: Reaction Norms Indirect Genetic Effects and Behavioural Synmentioning
confidence: 99%
“…Outcomes of conflict between individuals, and between sets of genes, are difficult to predict, but may include stable equilibria, tugs-or-war over resource allocation, one party 'winning' due to asymmetries in control over resource allocation, or continued conflict (e. g., Royle et al 2004;Smiseth et al 2008). Conflicts such as genomic imprinting also potentiate liability to phenotypes associated with disease (Crespi 2010), due to functional haploidy of imprinted genes, dysregulation of tug-of-war based systems that evolved in this context, and the expected general higher lability of epigenetic gene-expression control systems (based on methylation and histone modifications) compared to the lability of DNA alterations via mutation.…”
Section: Introductionmentioning
confidence: 99%